Analysis of the Economic Optimism of the Institutional Groups and Socio-Economic Systems - ENDOVITSKY, Dmitry A.; TABACHNIKOVA, Maria B.; TRESHCHEVSKY, Yuri I. (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The article aims at formulating general concept to assess the level of economic optimism of various institutional groups with a view to plan perspective development directions of socio-economic systems. The article analyzes the viewpoints of various institutional groups in a specific region of the Russian Federation (the Voronezh Region). Expert’s estimates served the basis to formulate development opportunities in the region (auspicious events). Respondents of big business, small business, regional authorities, local authorities, public organizations, and employees of budgetary organizations were experts in this survey. The outcomes of the study had two different aspects. First, we calculated economic optimism indices for each event auspicious for the region and each institutional group. Second, we tested methodological approach to assessment of event-based and institutional optimism that was applicable to any socio-economic systems.